Altering Tick Sizes, Liquidity, and Stock Return in Indonesia - sung suk kim (University of Merdeka Malang, 2022)
This study aimed to investigate the effect of tick-size altering on liquidity and stock return using the 2000-2018 Indonesia stock market (IDX) data. IDX was used to alter the tick size regime five times during the sample period. The results showed that a decrease in absolute tick size increases the liquidity estimated by the effective spread. The zero-return transaction frequency decreases consistently with a decrease in absolute tick size. The size also negatively impacts the abnormal stock return. Therefore, Fama-MacBeth approaches using individual firms' data show consistent results as the time series methods after controlling characteristic factors.